Waging peace : global adventures of a lifelong activist - Hartsough, David; Hollyday, Joyce; Dear, John, 1959-; Lakey, George; Butigan, Ken (Oakland, CA : PM Press, 2014)
David Hartsough knows how to get in the way. He has used his body to block Navy ships headed for Vietnam and trains loaded with munitions on their way to El Salvador and Nicaragua. He has crossed borders to meet the enemy in East Berlin, Castro's Cuba, and present-day Iran. He has marched with mothers confronting a violent regime in Guatemala and stood with refugees threatened by death squads in the Philippines. Hartsough's stories inspire, educate, and encourage readers to find ways to work for a more just and peaceful world. Inspired by the examples of Mahatma Gandhi and Martin Luther King Jr., Hartsough has spent his life experimenting with the power of active nonviolence. Engaging stories on every page provide a peace activist's eyewitness account of many of the major historical events of the past 60 years, including the Civil Rights and anti-Vietnam War movements in the United States as well as the little-known but equally significant nonviolent efforts in the Soviet Union, Kosovo, Palestine, Sri Lanka, and the Philippines. Waging Peace is a testament to the difference one person can make; however, it is more than one man's memoir: it shows how this struggle is waged all over the world by ordinary people committed to ending the spiral of violence and war.
Keywords: Hartsough, David -- Biography; Pacifists -- Biography; Peace movements -- Biography; Political activists -- Biography; Social justice -- Biography; War -- Prevention -- History -- Biography